Sikap Mahasiswa Program Studi PPKn Fkip Universitas Lampung Terhadap Program SM3T - Nur Anita Sari; Hermi Yanzi; Yunisca Nurmalisa (FKIP Unila, 2017)
The purpose of this research decrypt students attitude of program study ppkn fkip lampung university toward sm3t program. Research methodology that used in this research is descriptive with the quantitative approach, samples to be taken by 31 students. Data collection Technique using closed questionnaire and Likert scale questionnaire, then using formulas interval and the percentage to analyze. The results of the study is students attitude of program study fkip lampung university toward sm3t program can be described as agreed, because it was they support with the establishment of sm3t program in order to overcome a lack of teachers in the 3t . Tendency student acting toward sm3t program included in the category of neutral, so that the researcher and students having a positive attitude or support.Tujuan penelitian ini mendekripsikan Sikap Mahasiswa Program Studi PPKn FKIP Universitas lampung Terhadap Program SM3T. Metode penelitian yang digunakan dalam penelitian ini deskriptif dengan pendekatan kuantitatif, sampel yang diambil sebesar 31 mahasiswa. Teknik pengumpulan data menggunakan angket tertutup dan angket skala likert, kemudian untuk menganalisis menggunakan rumus Interval dan Persentase. Hasil penelitian menunjukan bahwa Sikap Mahasiswa Program Studi PPKn FKIP Universitas lampung Terhadap Program SM3T dapat dikategorikan setuju, hal ini dikarenakan mereka mendukung dengan dikeluarkannya program SM3T guna mengatasi kurangnya tenaga pendidik di daerah 3T.kecenderungan bertindak mahasiswa terhadap program SM3T masuk dalam kategori netral, maka menurut peneliti mahasiswa memiliki sikap yang positif atau mendukung.Kata kunci : mahasiswa, sikap, SM3T